(untitled) (Research, Society and Development, 2023)
This article brings the context of an education experienced in times of a pandemic, whose pedagogical practices worked at the moment caused ruptures in the act of teaching and learning. It was not transfer of knowledge, but possibilities for its construction. Intentional practices were developed that dialogued with the remote emergency period, as they were able to provide a more critical education, with an emancipatory character and, above all, with the use of Information and Communication Technologies (ICTs), which happened unevenly for the public school students. The mobilization of pedagogical practices during the pandemic period involved, firstly, understanding the relationship between the subjects of the teaching and learning process and the environment in which they were inserted. This work is, therefore, a part of the dissertation research presented in the Graduate Program in Teaching and Teacher Training IFCE/UNILAB. The objective of the article is to analyze the educational scenario of students and educators in the context of a health, social and economic crisis deepened by the covid-19 pandemic. We used bibliographic survey and participant observation in the construction of this article. The approach of this research has a qualitative character, since there will be exploratory data and strategies to approach reality. The results will be presented through images and words. We will also discuss here the teaching work during the pandemic, making a relationship with political issues and social movements around this class.